Pelatihan Digital Marketing Produk Mie Mokaf Bagi Imigran Digital Pada Lembaga Masyarakat Desa Hutan “Sumber Makmur” - Purbowo Purbowo; Miftachul Chusnah; Canggih Nailil Magfiroh (Lembaga Penelitian, Publikasi Ilmiah dan Pengabdian kepada Masyarakat (LP3M), 2024)
Digital marketing training for digital immigrants is a challenge because you are dealing with people who were born before digital existed. This is different from digital natives, who have been using information and communication technology media since birth, such as smartphones and laptops. The service activity aims to introduce applicable digital marketing to digital immigrant community groups by using frequently used social media, namely Facebook. The material that has been delivered includes product photos, creating product descriptions, and uploading to Facebook. Participants are female forest farmers under the auspices of the Forest Village Community Institution (LMDH)